CDR analysis using big data technology - Elagib, Sara B. (IEEE, 2016)
Call Detail Records (CDR) is a valuable source of information; it opens new opportunities for telecom industry and maximize its revenues as well as it helps the community to raise its standard of living in many different ways. However, we need to analyze CDRs in order to extract its big value. But CDRs has a huge volume, variety of data and high data rate, while current telecom systems are designed without these issues in mind. CDRs can be seen as Big Data source, and hence, it is applicable to use Big Data technologies (storage, processing and analysis) in CDR analytics. There are considerable research efforts to address the CDR analysis challenges. This paper presents the use of Big Data technology in CDR analysis by giving some CDR analytics based application examples, highlighting their architecture, the utilized Big Data tools and techniques, and the CDR use case scenarios.